ACCOUNTING PROFESSION: USING SWOT ANALYSIS APPROACH IN 5.0 SOCIETY ERA - Sari Nuzullina Rahmadhani (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The accounting profession has a very important role in various entities and sectors. This study aims to examine the existence of the accounting profession related to the presence of the 5.0 industrial revolution era. This research uses quantitative methods. The sample in this study were accountants who worked as accountant educators, public accountants and tax consultants in the city of Medan, totaling 150 people. As a result, it is known that the role of the accounting profession in the era of the industrial revolution 5.0 has been transformed into digital skills, applying new technology prototypes, learning by doing, international certification-based education, responsive to changes in industry, business and technology development, as well as curricula and learning based on digital skills. Accountant professional bodies need to encourage and facilitate continuous learning for accountants, for example through an online course or knowledge base that can be accessed widely and provides real-time and continuous updating of knowledge. This is necessary so that the accounting profession can continue to exist in an era of challenges. 5.0.